(untitled) (LEARNing Landscapes, 2016)
This piece explores the potential of ction as a powerful pedagogical tool within and beyond the academy. Drawing on professors’ examples, literary neuroscience, and my experience as an author of sociological ction and editor of the Social Fictions book series, I suggest how ction can be used to foster critical thinking, consciousness- raising, forge micro-macro connections, engage learners in deep re ection, teach substantive content, and promote understanding and empathy across di erences.